Penetapan Kadar Senyawa Epikatekin dalam Ekstrak Air Kulit Batang Faloak (Sterculia quadrifida R.Br.) Berbagai Varian sebagai Antihepatitis C - Dean, Muhajirin; Telussa, Arley Sadra; Malelak, Elric Brahm (Journal of Islamic Medicine, 2024)
Background: East Nusa Tenggara Province, Indonesia, is a common location for the faloak plant. Due to its epicatechin compounds, the faloak plant (Sterculia quadrifida R.Br) has potential for use as an anti-hepatitis C treatment. Objective: This study aims to identify the highest epicatechin content of faloak obtained from various places, to optimize the cultivation and processing of faloak plants into herbal antihepatitis C medicines. General therapy for hepatitis C causes side effects such as hemolytic anemia, pruritus, asthenia, neutropenia, myalgia, respiratory problems, cardiovascular disorders, and even teratogenic. Methods: Faloak plants obtained from 3 locations (Rote, Timor, and Semau Islands) were extracted with water solvent. The extracts were then analyzed by HPLC to measure epicatechin levels using standard. Results: All three samples from different islands demonstrated the presence of epicatechin, as indicated by their retention times matching the standard compound. The retention times for the Faloak water extracts from Rote, Timor, and Semau Islands were 12.420, 12.427, and 12.353, respectively. The assay results revealed that the sample from Rote Island had the highest concentration, measuring 24.810%. Conclusion: All faloak water extracts contain epicatechin, with the highest concentration found in faloak from Rote Island.